Aedes albopictus em área rural do Brasil e implicações na transmissão de febre amarela silvestre Aedes albopictus in rural zone of Brazil and its implication in the sylvatic yellow fever transmission - Almério de Castro Gomes; Marisa Dantas Bitencourt; Délsio Natal; Pedro Luis Silva Pinto; Luis Filipe Mucci; Marcia Bicudo de Paula; Paulo Roberto Urbinatti; José Maria Soares Barata (Universidade de São Paulo, 1999)
Durante estudos ecológicos sobre mosquitos anofelíneos no município de Bataguassu, Estado de Mato Grosso do Sul, foram encontradas larvas e adultos de Aedes albopictus. Pela primeira vez sua introdução ocorre numa área enzoótica do vírus selvático da febre amarela no Brasil. Isto sugere risco potencial para transferência desse vírus para área urbana infestada com Aedes aegypti. Larvae and adult forms of Aedes albopictus were found during ecological study of anopheline mosquitos in the rural zone of the state of Mato Grosso do Sul in Brazil. This occurrence was registered, for the first time in Brazil, in an enzoootic area if sylvatic yellow fever virus. This implies a potential risk of the transfer of this virus to an urban area infested with Aedes aegypti.